Overweight and Obesity Associated Factors among High School Students: A Cross Sectional Study in Erbil (Medico Legal Update, 2020)
Introduction: The overweight of youth and teens is one of the fundamental issues in the world that seems to be lifestyle and Inactivity of the causes of overweight. The purpose of this study was to investigate the causes of obesity / overweight in high school students.Methods: In this cross-sectional study, 1,000 students in the age range 16-18 years of Erbil, Iraq in 2016-2017 were randomly selected. Data were collected via questionnaire. Data were examined using SPSS 22 for windows and analyzed by appropriate statistical tests.Results: surveys demonstrated that 30% of youth aged 16 to 18 were overweight or obese. About 30 percent met physical activity guidelines; however, physical activity was not associated with overweight or obesity in this sample. Computer games, watching TV (0.007) and irregular sleep (P-value=0.019) were among other known factors/ affecting obesity/overweight in this study.Conclusions: According to findings, we concluded that a trend towardbeing overweight/ obese in youth and there are many factors involved, such as irregular sleep and lack of mobility in overweight.